2020
DOI: 10.1177/0954405420949221
|View full text |Cite
|
Sign up to set email alerts
|

A roll-bending approach to suppress the edge cracking of silicon steel in the cold rolling process

Abstract: The range of roll-bending that inhibits the edge cracking of high-silicon (3.0 wt%) steel strip during cold rolling was investigated by performing a pilot cold rolling test. In the rolling test, roll-bending was emulated by lathe-machining the work roll surface to be concave (corresponding to negative roll-bending) or convex (corresponding to positive roll-bending). Crack growth length that propagated during rolling and crack growth direction were measured. Three-dimensional finite element analysis coupled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The elastic modulus of the strip was 190 GPa, the density was 7650 kg/m 3 , and Poisson's ratio was 0.3. Byon et al [8] showed that the pilot cold rolling test and FE analysis results were consistent when the element size in the x and z-directions around the notch tip of high silicon steel strip was 0.05 mm, respectively. Hence, mesh convergence test in this study was performed to determine the appropriate number of elements in the strip thickness direction.…”
Section: Fe Simulation Of Cold Rollingmentioning
confidence: 92%
See 3 more Smart Citations
“…The elastic modulus of the strip was 190 GPa, the density was 7650 kg/m 3 , and Poisson's ratio was 0.3. Byon et al [8] showed that the pilot cold rolling test and FE analysis results were consistent when the element size in the x and z-directions around the notch tip of high silicon steel strip was 0.05 mm, respectively. Hence, mesh convergence test in this study was performed to determine the appropriate number of elements in the strip thickness direction.…”
Section: Fe Simulation Of Cold Rollingmentioning
confidence: 92%
“…Kang et al [41] calibrated a two-parameter ductile fracture model through tension test and FE analysis for stress triaxiality due to various notch changes in tensile specimens. Unlike the tension test, since the range of stress triaxiality in rolling is −1.2 to 1.2 [8], the effect on fracture is affected not only by stress triaxiality but also by the Lode parameter [42,43]. Therefore, a ductile fracture criterion that reflects the Lode parameter is required, and related models [10,29,34,44] are the maximum shear model [44], the modified Mohr-Coulomb (MMC) fracture criterion [10] and so on.…”
Section: D Fracture Locusmentioning
confidence: 99%
See 2 more Smart Citations
“…Some scholars have investigated machining and rolling via finite element analysis. Byon et al 10 used finite element software to simulate the cold rolling process of steel strips, predicted the length and direction of strip edge crack extension with the ductile fracture criterion, and performed cold plate rolling test to validate the reliability of finite element analysis. The result shows that using a concave profile which corresponds to a negative roll can reduce the occurrence of edge cracks in the strip during cold rolling.…”
Section: Introductionmentioning
confidence: 99%